2013
DOI: 10.3892/mmr.2013.1366
|View full text |Cite
|
Sign up to set email alerts
|

Signaling network of OSW-1-induced apoptosis and necroptosis in hepatocellular carcinoma

Abstract: The compound 3β, 16β, 17α-trihydroxycholest-5-en-22-one 16-O-(2-O-4-methoxybenzoyl-β-D-xylopyranosyl)-(1→3)-(2-O-acetyl-α-L-arabinopyranoside (OSW-1) is a member of the cholestane saponin family that was created in the bulbs of Ornithogalum saudersiae. OSW-1 has previously been shown as cytotoxic against numerous types of malignant cells, however, its antitumoral mechanisms remain unclear. The present study aimed to examine the potential changes in the gene expression of a hepatocellular carcinoma (HCC) cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Although the apoptosis was not induced by Caspase-family and p53 pathway, the apotosis did happen [19]. To elucidate and confirm the molecular mechan- Jeong's study showed that upon FR122047 treatment, the selective COX-1 inhibitor, there were apparent increases in the ratio of Bax to Bcl-2, mitochondrial Cytochrome C release, and apoptosis in MCF-7 cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although the apoptosis was not induced by Caspase-family and p53 pathway, the apotosis did happen [19]. To elucidate and confirm the molecular mechan- Jeong's study showed that upon FR122047 treatment, the selective COX-1 inhibitor, there were apparent increases in the ratio of Bax to Bcl-2, mitochondrial Cytochrome C release, and apoptosis in MCF-7 cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively new form of necrosis has been characterized as 'necroptosis' (11,12). Necroptosis is a newly identified type of programmed cell death initiated by the activation of apoptosis induced by binding of tumor necrosis factor (TNF) or Fas to its receptor, referred to as a regulated form of necrosis, which is dependent on the serine-threonine kinase receptor-interacting protein 1 (RIP1) (13,14). Necroptosis exhibits morphological characteristics, which resemble necrosis and can be specifically inhibited by a small molecule, necrostatin-1 (Nec-1), which targets RIP1 (15).…”
Section: Introductionmentioning
confidence: 99%
“…For the apoptosis assay, LoVo cells (1x10 6 ) were treated with 90 and 180 ng/ml of OSW-1 for 24 h. Then, the cells were collected and washed with cold PBS and resuspended in 100 µl of binding buffer. Finally, 5 µl of Annexin V-FITC and 5 µl of propidium iodide staining solution were added for 15 min in the dark.…”
Section: Cellular Proliferationmentioning
confidence: 99%
“…OSW-1 is classified as cholestane glycoside chemical structure formula: [3β,16β,17α-trihydroxycholest-5-en-22-one16-O-(2-O-4-methoxybenzoyl-β-D-xylopyranosyl)-(1→3)-(2-O-acetyl-α-Larabinopyranoside)]. Several studies have suggested that OSW-1 has a potent anti-proliferative effect against a variety of tumor cell lines, such as leukemia, pancreatic cancer, malignant brain tumor, and hepatocellular carcinoma cells, but is less toxic to non-malignant cells in vitro (5,6); however, it is so difficult to isolate the compound in certain stages that the application is restricted to research. Recent studies have shown that the synthesis of OSW-1 and its derivatives has gradually improved; however, this finding provides the premise for a possible therapeutic application for OSW-1 in the future (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%